Physical-chemical stability test on spray gel with active compound ethyl p-methoxycinnamate (Kaempferia galanga Linn.) and menthol, using combination gelling agent na cmc and copovidone - Suryani, Nelly; Komala, Ismiarni; Akhsani, Luthfia Wikhdatul; Dahlizar, Sabrina; Betha, Ofa Suzanti; Rahmat, Deni (Faculty of Pharmacy, Universitas Pancasila, 2024)
The major component of galangal rhizome (Kaempferia galanga Linn) is ethyl p-methoxycinnamate (EPMS), which amounts to 80.05%. Significant anti-inflammatory activity is exhibited by EPMS from galangal rhizome through the inhibition of carrageenan-induced mouse edema and the inhibition of IL-6 production. EPMC is recognized for various pharmacological effects, particularly its potential as a wound healing agent due to its anti-inflammatory properties. The choice of spray was made because it meets the characteristics of anti-inflammatory preparations in the wound healing process. The preparation must be moist, easily adjusted to the shape of the wound (flexible), sterile, and evenly distributed, covering the tissue, and can be easily removed from the tissue, including the wound. A spray gel dosage form was formulated with varying concentrations of the gelling agent Na CMC, F1 (0.5%), F2 (1.0%), and F3 (1.5%). Physical stability was evaluated at room temperature storage on days 0, 7, 14, and 21. Organoleptics, homogeneity, viscosity, pH, spray pattern, adhesive spread ability, centrifugation test, and cycling test were evaluated. Chemical stability evaluation was carried out using UV-Vis spectrophotometry to assess the EPMS levels in the preparation. The results of the physical evaluation showed that all formulas were stable in terms of organoleptics, homogeneity, and pH, which was in the range of 6.6–7.1; the weight per spray was uniform and relatively stable in centrifugation and cycling tests. The use of a combination of sodium carboxymethylcellulose and copovidone can produce a spray gel preparation of a good aromatic ginger (Kaempferia galanga Linn) crystal with a 1%.